PENGARUH KECERDASAN EMOSIONAL, SELF CONFIDENCE, DAN LITERASI DIGITAL TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA KELAS X AKUNTANSI SMK NEGERI 4 SURABAYA - Rosyida, Luthfi; Bahtiar, Moh Danang (Jurnal Pendidikan Ekonomi (JURKAMI), 2024)
The quality of education in Indonesia is relatively low as seen from the PISA score in 2022 ranked 68 out of 81 countries, where reading scores (359), mathematics scores (366), and science scores (383). One of the causes is in students' critical thinking factors. This study aims to find out and analyze the variables that are expected to affect students' critical thinking skills. The population of this study is 106 students in class X Accounting at SMK Negeri 4 Surabaya. The sample is 84 students who are selected through a simple random sampling technique. Quantitative research method with the type of explanatory research. The results of the study showed that: 1) Simultaneously, emotional intelligence, self-confidence, and digital literacy had a significant effect on students' critical thinking skills. 2) Partially, emotional intelligence, self-confidence, and digital literacy have a significant effect on students' critical thinking skills. Therefore, it is hoped that all students and educators are aware of the importance of these factors and can direct students to be able to think critically more in learning.